Managers’ Moral Obligation of Fairness to (All) Shareholders: Does Information Asymmetry Benefit Privileged Investors at Other Shareholders’ Expense? - Evans, Jocelyn D.; Perrault, Elise; Jones, Timothy A. (2017)
Drawing on ethical principles of fairness and integrative social contracts theory, moral obligations of fair dealing exist between the firm and all shareholders. This study investigates empirically whether privileged investors of publicly traded firms engage in legal, but morally questionable, trading that at the expense of non-privileged institutional or atomistic investors. In this context, we define privilege as the access to material, nonpublic earnings surprise information. Our results show that the opportunity for procedural unfairness (e.g., the likelihood of an earnings surprise and information asymmetry) increases with the presence of privileged investors. However, this procedural unfairness does not appear to lead to distributive unfairness even though the level of abnormal trading also increases with the presence of privileged investors. That is, our findings suggest that other shareholders are in fact better off from an outcome perspective given that the abnormal stock price returns upon the announcement of an earnings surprise are either more positive (in response to a favorable surprise) or less negative (in the case of an unfavorable surprise) when the firm has a high proportion of privileged investors. We extract the important implications of our study for future research on the fairness of capital markets and information asymmetry amongst classes of investors, as well as for public policy.
Keywords: Moral Obligation; Earnings announcement; Fiduciary Duty; Integrative Social Contracts Theory (ISCT); Information Asymmetry; Fairness